Evolutionary Consequences of Desiccation Resistance in the Male Ejaculate - Perez Staples, Diana Folger (2018)
Avoiding water loss for insects is critical for survival. Selection for reduced water loss will depend on trade-offs between resources allocated for reproduction and those allocated for resisting desiccation. However, we lack knowledge on how selection for desiccation resistance can affect the male ejaculate. Furthermore, as male ejaculate composition is complex, desiccation resistant females could evolve traits that enable them to derive longevity benefits from mating. Here, we assessed how selection for desiccation resistance impacts male testes and accessory gland size, protein content of these organs, female sperm storage and male ability to inhibit female remating behavior, in the Mexican fruit fly Anastrepha ludens. Additionally, we tested if mating increased longevity and fecundity in desiccation resistant females. Males selected for resistance to desiccation stress had smaller accessory glands and seminal vesicles and females mating with these males stored less sperm compared to control males. Females mating with resistant males had lower fecundity compared to females mating with control males. Desiccation resistant females lived longer than control females, yet this was irrespective of mating. Rapid evolutionary responses to hydric stress can have correlated effects in reproductive capabilities, which are not restricted to pre-copulatory traits. Trade-offs between resistance to desiccation stress are reflected in decreased allocation of resources to reproductive organs. Thus, production of the ejaculate may be costly for A. ludens males. Knowledge on the evolution of ejaculate traits and reproductive organ size in response to directional selection for desiccation resistance, will aid our understanding of differential sex-specific responses to environmental stress.